A four leaf clover shape reflectarray antenna for X Band applications - Singh U.; Mali R.; Meshram M.K. (My University, 2025)
This paper communicates a design of a nature-inspired four-leaf clover shape radiating element and further incorporates it into making RA. It is a low-profile design on a single layer and possesses high gain. The radiating patch is a 1.56 mm thick Rogers RT/duroid 5880 of dielectric constant Ɛr=2.2 and tanδ = 0.025. It works well for the intended center frequency at 10 GHz of the X band (8 to 12 GHz). This circular aperture RA is of diameter 300 mm with 316 reradiating units arranged on it. From simulated results, the side lobe level and cross-polarization level in the E plane are below 13 dB and 60 dB separately for operating frequency. Further maximum gain of 25.46 dBi is obtained and aperture efficiency is 35.68 % at 10 GHz. While a 3 dB gain bandwidth of 18 % is attained. © 2024 IEEE.